Causal Effects of Triz Engineering Design Knowledge on Engineering Design Creativity Among the Undergraduate Engineering Students - Keong Chee Sheng (2019)
Malaysia is heading towards innovative economy that emphasizes creativity and innovation. Engineers are required to be more creative and innovative to be globally competitive. As such, engineering education is instilling creativity and innovative skills among undergraduate engineering students through engineering design using the Theory of Inventive Problem Solving (TRIZ). TRIZ has been taught in engineering courses in several higher institutions in Malaysia. However, there is insufficient empirical study on the causal effects of TRIZ engineering design knowledge on the actual improvement of engineering design creativity among undergraduate engineering students in Malaysia. The theoretical framework of the present study consists of one exogenous construct (TRIZ engineering design knowledge), two mediating constructs (engineering design self-efficacy and intrinsic motivation), one moderating construct (instructor support) and one endogenous construct (engineering design creativity). Survey was carried out on 302 undergraduate engineering students in three local institutions who have received TRIZ training. The data were analysed through a process of multivariate analysis namely Structural Equations Modeling (SEM) using Analysis of Moment Structures (AMOS) software version 21. The result showed that TRIZ engineering design knowledge, engineering design self-efficacy and intrinsic motivation have significant positive effect on engineering design creativity. Engineering design self-efficacy has significant positive effect on intrinsic motivation. Both engineering design self-efficacy and intrinsic motivation partially mediated the relationship between TRIZ engineering design knowledge and engineering design creativity. The instructor support does not act as the moderator between TRIZ engineering design knowledge and engineering design creativity. The findings contribute significantly to the teaching of TRIZ in engineering education. (Abstract by Author)